(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
This article seeks to establish a theoretical and practical connection between the ideas of Edgar Morin and Gianni Rodari in the context of teaching literary writing during the early years of elementary school. Both thinkers emphasize the profound value of literature. Morin (2005, 2011, 2015a) advocates for its role in fostering self-knowledge, revealing human multidimensionality, promoting empathy toward others, and illuminating the complexities of interpersonal relationships and the world at large. Rodari (1982, 2000, 2009), in turn, focused on devising techniques, reflections, and activities to make literature accessible to children, emphasizing the playfulness of language, logical reasoning, aesthetic appreciation, and the cultivation of creativity, imagination, and fantasy. Drawing on examples of pedagogical practices, this article illustrates the viability of nurturing children’s creative expression within a stimulating environment, one that challenges them to envision themselves as authors and critical thinkers while equipping them for active societal engagement. By integrating these practices through the lens of complexity and inventive interaction with literary texts, we advocate for teaching literature as interconnected experiences that seamlessly link reading and writing.